2012
DOI: 10.1136/bmjopen-2012-001368
|View full text |Cite
|
Sign up to set email alerts
|

Inter-rater and test–retest reliability of quality assessments by novice student raters using the Jadad and Newcastle–Ottawa Scales

Abstract: IntroductionQuality assessment of included studies is an important component of systematic reviews.ObjectiveThe authors investigated inter-rater and test–retest reliability for quality assessments conducted by inexperienced student raters.DesignStudent raters received a training session on quality assessment using the Jadad Scale for randomised controlled trials and the Newcastle–Ottawa Scale (NOS) for observational studies. Raters were randomly assigned into five pairs and they each independently rated the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(131 citation statements)
references
References 28 publications
(26 reference statements)
2
122
0
1
Order By: Relevance
“…Alongside the effect of such factors upon the interpretation of results derived from a quality assessment instrument, the Newcastle-Ottawa tool has received particular criticism. These criticisms range from the tool's focus upon the generalizability of a given sample to the general population as opposed to its internal validity (59) to the arbitrary nature of some questions that appear to weaken interrater reliability (60,61). With these limitations in mind, the Newcastle-Ottawa quality assessment tool should be considered only as a rough guide for readers as opposed to a definitive measure of study quality.…”
Section: Limitationsmentioning
confidence: 99%
“…Alongside the effect of such factors upon the interpretation of results derived from a quality assessment instrument, the Newcastle-Ottawa tool has received particular criticism. These criticisms range from the tool's focus upon the generalizability of a given sample to the general population as opposed to its internal validity (59) to the arbitrary nature of some questions that appear to weaken interrater reliability (60,61). With these limitations in mind, the Newcastle-Ottawa quality assessment tool should be considered only as a rough guide for readers as opposed to a definitive measure of study quality.…”
Section: Limitationsmentioning
confidence: 99%
“…Total score was the sum of the points assigned to each word in the instrument (0 or 1). Inter-and intra-rater agreement rates higher than 0.85 were considered acceptable levels of agreement 11 (according to the literature, kappa coefficient > 0.80 is considered to be near-perfect agreement 12 and ICC > 0.75 is an excellent agreement 13 ). Furthermore, the percentage of agreement for each word of the BREALD-30 was calculated considering all interviewers in relation to the gold standard researcher.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…20 In the present study, the minimum ICC values for intra-rater agreement of 0.990 and inter-rater agreement of 0.975 are excellent. 13 Although the more heterogeneous the individuals' measures the higher the ICC, this characteristic has been seen as an advantage because it may reduce the disagreement in relation to the magnitude of the measure. 21 The intra rater agreement is necessary because of the subjectivity of some evaluation methods and because of the examiner's specific conditions, such as fatigue, which may lead to inconsistent results.…”
mentioning
confidence: 99%
“…The internal consistency indicated that the items or dimensions of the questionnaire measured similar variables. The ICC indicated a good value (≥ 0.4) (22). The Cronbach's alpha was reported 0.92.…”
Section: Discussionmentioning
confidence: 99%